Antibacterial Effect of Lawsonia inerims linn. (Henna) Using Three Types of Leaf Extract In Vitro - Malik, S. N. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study was done to investigate the antibacterial effect of the three types of Lawsonia inermis linn (henna) leaf extracts (water, methanol and chloroform) in different concentrations (40, 80, 120) mg/ml against four strains of bacteria (Staphyllococus aureus, Bacillus subtilis, Pseudomonos aerogenosa and Eschorichia coli) in vitro using ager well diffusion method. Water extract showed the highest antibacterial activity, followed by  methanol extract, while the chloroform extract showed the lowest activity. The maximum inhibition zone of water extract was observed against , Pseudomonos aerogenosa (25mm) in the concentration (120) mg/ml, while the minimum zone of inhibition (9mm) was in Bacillus subtilis in the same concentration.  The growth of all bacteria was inhibited by varying degrees with the increase of the extract's concentrations. These results confirm the antibacterial activity of henna leaves and support the traditional use of the plant in therapy of bacterial infections.